Low-carbon ultra-high performance concrete and preparation method thereof

CN122916558APending Publication Date: 2026-10-16HENAN XUANXUAN HAOCHENG BUILDING MATERIALS TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611376240.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

具体要解决的技术问题包括:解决传统PCE减水剂在含泥骨料体系中分散能力下降的问题;消除APEG-PCE体系导致的塑化延迟现象;实现盾构渣土、粉煤灰等工业固废在UHPC中的高值化利用;降低UHPC的碳排放和原材料成本,保持超高性能

Benefits of technology

1.本发明采用4-磺酰基杯[6]芳烃对聚羧酸减水剂进行改性,利用杯[6]芳烃刚性大体积骨架(空腔约0.7nm)形成空间位阻效应,有效抑制PCE的PEG支链向蒙脱土层间的插层吸附,解决了传统PCE在含泥体系中分散能力大幅下降的技术难题。杯芳烃的磺酸基团同时增强分子亲水性,促进水泥颗粒表面快速吸附。试验表明,蒙脱土掺量1.5%时,改性PCE净浆流动度保持率达84.2%,显著优于传统PCE的45.7%和4-叔丁基杯[4]芳烃改性PCE的61.2%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of low-carbon ultra-high performance concrete and preparation method thereof, belong to building material technical field.The concrete includes by weight parts: shield slag 100 parts, Portland cement 6~10 parts, slag 2~6 parts, fly ash 1~2 parts, alkali activator 2 parts, calixarene modified polycarboxylic acid water reducing agent 2~2.5 parts, water 25~35 parts;Wherein calixarene modified polycarboxylic acid water reducing agent is prepared by 4-sulfonyl calix [6] arene monoolefin and TPEG Copolymerization;Utilize the steric hindrance effect of calix [6] arene rigid skeleton and inhibit PCE side chain intercalation between clay layers, give system excellent anti mud performance;Meanwhile, accelerate PCE adsorption on cement particle surface, eliminate plasticizing delay.The application makes full use of shield slag and fly ash, carbon emission reduction rate reaches 54.6%~63.9%, 28d compressive strength 118.7~145.6MPa, suitable for prefabricated component and tunnel engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to a low-carbon ultra-high performance concrete and its preparation method. Background Technology

[0002] Ultra-high performance concrete (UHPC), as a novel cement-based material, possesses excellent properties such as ultra-high strength (up to 120 MPa or more), high durability, and strong self-healing ability for microcracks, making it promising for applications in bridges, high-rise buildings, and national defense engineering. However, traditional UHPC requires large amounts of cement and silicate sand, resulting in high material costs. Furthermore, the production process of silicate cement releases a significant amount of CO2, which is detrimental to the sustainable development of the construction industry.

[0003] On the other hand, with the acceleration of urbanization, the large amount of tunnel boring machine (TBM) excavation waste generated during TBM construction has become an urgent urban environmental problem. TBM excavation waste has a high moisture content and complex composition, and traditional landfill disposal methods not only occupy land resources but also pose environmental pollution risks.

[0004] Polycarboxylate superplasticizers (PCE) are widely used in the preparation of ultra-high-temperature polycarbonate (UHPC) due to their advantages such as low dosage, high water reduction rate, and strong molecular structure designability. However, PCE is quite sensitive to clay impurities in aggregates. Studies have shown that the adsorption mechanism of PCE by montmorillonite is mainly the intercalation adsorption of PCE's long polyethylene glycol branches onto the layered crystals of montmorillonite. The intercalation reaction increases the interlayer spacing, resulting in a loss of flowability. The layered structure of montmorillonite endows it with extremely strong adsorption capacity; the specific surface area per gram of montmorillonite can reach hundreds of square meters, which is the structural basis for intercalation adsorption.

[0005] In response to the above problems, the following improvement solutions have been proposed in the prior art: The patent with publication number CN113583190A provides a 4-tert-butylcalix[4]aromatic modified polycarboxylate superplasticizer and its preparation method. It discloses a polycarboxylate compound polymerized from vinylcalixarene and polyether macromonomer, namely 4-tert-butylcalix[4]aromatic modified polycarboxylate superplasticizer. The calixarene group is introduced by first chlorinating the polyether macromonomer and then grafting calix[4]aromatics. The calixarene structure is introduced through the side chain to increase the steric hindrance.

[0006] However, existing technologies have not specifically addressed the plasticization delay phenomenon (slump increases first and then decreases) that is common in APEG-PCE systems, which affects construction efficiency. Furthermore, existing low-carbon UHPC research mainly focuses on optimizing the proportion of cement substitutes for solid waste, but there is still a lack of systematic solutions to problems such as the interference of clay impurities in shield tunnel slag on the dispersion performance of PCE and the compatibility of water-reducing agents with alkali-activated systems. Summary of the Invention

[0007] This invention addresses the shortcomings of existing technologies by providing a low-carbon ultra-high performance concrete and its preparation method. Specifically, the technical problems to be solved include: addressing the issue of decreased dispersion ability of traditional PCE water-reducing agents in mud-containing aggregate systems; eliminating the plasticization delay phenomenon caused by the APEG-PCE system; realizing the high-value utilization of industrial solid wastes such as tunnel boring machine slag and fly ash in UHPC; reducing carbon emissions and raw material costs of UHPC while maintaining ultra-high performance.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: A low-carbon ultra-high performance concrete has the following raw material composition (parts by weight): Tunnel boring machine excavated soil (after treatment, moisture content ≤40%, particle size ≤3mm): 100 parts; Silicate cement (P·O 42.5 or P·O 52.5): 6-10 parts; S95 grade granulated blast furnace slag: 2-6 parts; Fly ash (Grade I or II): 1-2 parts; Alkali activator (sodium silicate modulus 2.4–3.2, NaOH concentration 8–12 mol / L or a mixture thereof): 2 parts; Poly(MAST) series calixarene-modified polycarboxylate superplasticizer: 2-2.5 parts; Water: 25-35 parts.

[0009] Preferably, the shield tunneling waste soil mentioned in this invention refers to engineering waste soil generated during shield tunneling construction of urban subways, tunnels, etc., whose main mineral components are silicate minerals such as quartz, feldspar, montmorillonite, and illite, and is rich in SiO2 and Al2O3. This invention pre-treats the shield tunneling waste soil before use (the pre-treatment method is detailed below), ensuring a moisture content ≤40% and a particle size ≤3mm. In this invention, the shield tunneling waste soil serves the dual function of fine aggregate and auxiliary cementitious material: its fine particles (<0.075mm) can undergo a geological polymerization reaction under alkaline activation conditions, while its coarse particles (0.075~3mm) act as a fine aggregate filling skeleton.

[0010] Furthermore, shield tunneling excavated soil contains a large amount of moisture, stones, debris, and has uneven particle size distribution, requiring pretreatment before use. The specific pretreatment steps are as follows: The first step is to collect the tunnel boring machine excavated soil and remove impurities such as stones, concrete blocks, steel bars, and plastics manually or mechanically. Then, water is added and stirred to adjust the moisture content to 50% to 60%, making the excavated soil a flowing slurry that is easy to screen later.

[0011] The second step is to sieve the prepared mud with a sieve size of 2mm to remove coarse particles larger than 2mm, ensuring that the particle size of the treated slag meets the requirements for fine aggregate gradation.

[0012] The third step involves mechanical dewatering using filter press or centrifugation, supplemented by electroosmosis or vacuum dewatering, to reduce the moisture content of the sludge cake to 60%–75%. Mechanical dewatering is the main method for removing free water from slag, while electroosmosis or vacuum dewatering can further reduce the moisture content and improve processing efficiency.

[0013] The fourth step is to further process the dehydrated slag to a moisture content of ≤40% and a particle size of ≤3mm, which is the pretreated shield tunnel slag that can be used for the preparation of UHPC in this invention.

[0014] Preferably, this invention uses P·O 42.5 or P·O 52.5 silicate cement as the main cementing material to provide early strength and calcium source. When the cement content is less than 6 parts, the alkalinity of the system is insufficient to fully activate the pozzolanic activity of slag and fly ash, and the amount of hydration products is insufficient to guarantee ultra-high performance. When the cement content is more than 10 parts, carbon emissions increase significantly, failing to meet the low-carbon target, and excessive early hydration heat may cause temperature cracks.

[0015] Preferably, the slag is a powder material obtained by granulating blast furnace slag (obtained through water quenching and rapid cooling) and grinding it to a specified fineness. Its main chemical components are CaO, SiO2, Al2O3, and MgO, and it possesses potential hydraulic properties. Under the action of an alkaline activator, the glassy structure in the slag deagglomerates, releasing CaO. 2+ The slag, along with aluminosilicate ions, participates in the hydration reaction to generate CSH and CASH gels. The addition of slag replenishes the calcium source in the system, compensating for the low calcium content of fly ash. At the same time, its aluminum-rich properties are conducive to the formation of products such as hydrated calcium aluminate, thereby improving the density of the system.

[0016] Preferably, the present invention uses Grade I or Grade II fly ash, which is the fine ash collected from the flue gas after coal combustion in coal-fired power plants. Its main components are SiO2, Al2O3, and Fe2O3. The glass microsphere morphology imparts a good ball bearing effect, improving the fluidity of the freshly mixed slurry. The active silica-alumina components of the fly ash undergo a pozzolanic reaction under the dual action of alkali activation and Ca(OH)2 generated during cement hydration, generating additional CSH gel to fill the pores. However, the fly ash content should not exceed 2 parts (relative to 100 parts of slag), otherwise early strength development will be slow.

[0017] Preferably, the alkaline activator used in this invention is sodium silicate (water glass, modulus 2.4–3.2), sodium hydroxide (concentration 8–12 mol / L), or a mixed solution thereof. The mechanism of action of the alkaline activator is as follows: in an alkaline environment (pH > 13), the silicon-oxygen bonds (Si-O) and aluminum-oxygen bonds (Al-O) in the tunnel boring machine slag and fly ash break and depolymerize into silicate ions (SiO4). 4- ) and aluminate ions (AlO4)5- The polymers then rebond through a condensation reaction to form a three-dimensional network structure of aluminosilicate polymers (geopolymers). This reaction proceeds synergistically with the cement hydration reaction, jointly contributing to the mechanical strength.

[0018] Preferably, the dosage of the water-reducing agent of the present invention is calculated based on the total amount of cementitious materials (cement + slag + fly ash). When the dosage of the water-reducing agent is less than 1.5% of the cementitious materials (corresponding to less than 2.0 parts), the dispersion effect is insufficient, and the particles cannot be fully wetted and dispersed; when the dosage is more than 3.0% of the cementitious materials (corresponding to more than 2.5 parts), although the fluidity is improved, the economy decreases and there is a risk of segregation. The preferred dosage is 2.0% of the cementitious materials.

[0019] Preferably, the amount of water used for mixing is controlled by the water-cement ratio as the final control indicator. In this invention, the water-cement ratio is controlled within the range of 0.30 to 0.45. When the water-cement ratio is below 0.30, the viscosity of the paste is too high, resulting in insufficient workability; when the water-cement ratio is above 0.45, excess free water forms capillary pores after hardening, severely reducing strength and durability.

[0020] Preferably, the Poly(MAST) series copolymers of the present invention are calixarene-modified polycarboxylate superplasticizers obtained by free radical copolymerization of 4-sulfonyl calix[6] aromatic monoene (monomer M) and isopentenyl polyoxyethylene ether (TPEG, molecular weight 2400) at different feed ratios. The design concept of this series of copolymers is: to provide steric stabilization effect and dispersion retention ability with TPEG long chain, to provide carboxyl anchoring groups with acrylic acid (through electrostatic adsorption on the surface of cement particles), to provide additional sulfonic acid hydrophilic groups with sodium methacrylate, and to provide rigid large-volume side chains with 4-sulfonyl calix[6] aromatic monoene to generate steric hindrance effect to inhibit clay intercalation.

[0021] Furthermore, this series of copolymers includes: Poly(MAST)-0: The molar ratio of monomer M to TPEG is 0:100 (i.e., unmodified PCE). Poly(MAST)-17: The actual molar ratio of monomer M to TPEG is approximately 0.17:0.83; Poly(MAST)-22: The actual molar ratio of monomer M to TPEG is approximately 0.22:0.78; Poly(MAST)-26: The actual molar ratio of monomer M to TPEG is approximately 0.26:0.74; Poly(MAST)-33: The actual molar ratio of monomer M to TPEG is approximately 0.33:0.67; Taking Poly(MAST)-26 as an example, the specific preparation steps are as follows: The first step is to prepare the monomer solution. 111.3g of TPEG (molecular weight 2400, about 0.0464mol) and 19.2g of 4-sulfonylcalix[6] aromatic monoene (molecular weight about 1151.73, about 0.0167mol) were dissolved in 160mL of deionized water. The mixture was then added to a 500mL four-necked round-bottom flask equipped with a stirrer, reflux condenser, and double dropper. The temperature was raised to 60℃ and 1.5g of 30% hydrogen peroxide was added. The hydrogen peroxide decomposed under heating conditions to generate hydroxyl radicals, which initiated the polymerization reaction.

[0022] The second step is to prepare the dropping solutions. Solution I is prepared by dissolving 11g of acrylic acid and 2g of sodium methacrylate sulfonate in 30mL of deionized water, providing carboxyl and sulfonic acid functional monomers. Solution II is prepared by dissolving 0.5g of 3-mercaptopropionic acid and 0.25g of ascorbic acid in 45mL of deionized water. 3-mercaptopropionic acid acts as a chain transfer agent to regulate the polymer molecular weight, while ascorbic acid acts as a reducing agent to form a redox initiation system with hydrogen peroxide to lower the activation energy.

[0023] The third step is isothermal dropwise polymerization. Maintaining the system temperature at 60°C, two peristaltic pumps are used to continuously add solution one and solution two, respectively, for 3 hours and 3.5 hours. The dual-drip nozzle design ensures the simultaneous addition of the initiator and monomer, which is beneficial for the uniformity of the copolymer composition. After all additions are complete, the mixture is kept at the temperature and stirred for another hour to ensure complete monomer conversion.

[0024] The fourth step is neutralization and discharge. The reaction solution is cooled to room temperature, and the pH is adjusted to 6.5-7.0 using a 30% sodium hydroxide aqueous solution to convert the carboxyl group into sodium carboxylate, thereby improving the water solubility and dispersibility of the water-reducing agent. The resulting liquid is the sulfonyl calixarene-modified PCE copolymer Poly(MAST)-26, with a solid content of approximately 40%.

[0025] Causes of delayed plasticization: The APEG-PCE system often exhibits delayed plasticization in the initial stage of cement paste, meaning that the paste fluidity initially increases (within 0-15 min) and then continuously decreases. There are two main reasons for this: First, the adsorption of PCE molecules on the surface of cement particles requires a certain amount of time to establish (adsorption kinetics limitation). Initially, the adsorption amount is insufficient, but as time progresses, adsorption gradually increases, resulting in a brief increase in fluidity. Second, in the clay-containing system, the adsorption of PCE by the clay continues. When adsorption-desorption reaches dynamic equilibrium, the effectively dispersed components are gradually consumed, fluidity begins to decrease, and ultimately, slump loss accelerates.

[0026] Mechanism of eliminating plasticizing delay by calixarene modification: This invention eliminates plasticizing delay synergistically from the following two aspects by introducing sterically hindered calixarene monomers: First, it accelerates initial adsorption. The sulfonic acid group (-SO3H) on the calixarene skeleton endows the PCE molecule with stronger hydrophilicity, increasing the wetting and adsorption rate on the cement particle surface. Simultaneously, the presence of the rigid side chain of the calixarene increases the hydrodynamic volume of the PCE molecule, slightly reducing its diffusion coefficient in solution. More importantly, the sulfonic acid group reacts with the Ca2+ on the cement particle surface... 2+ The rapid complexation significantly shortens the adsorption equilibrium time. Therefore, modified PCE can be rapidly adsorbed onto the surface of cement particles in the initial stage of water addition and mixing, and immediately exert its dispersing effect without undergoing a long adsorption establishment process, thus eliminating the initial adsorption stage from the source.

[0027] Second, it inhibits continuous consumption. The steric hindrance effect of calixarene effectively inhibits the intercalation adsorption of PEG side chains into the montmorillonite layers, keeping the effectively dispersed components stable in the clay-containing system and preventing continuous decay due to clay adsorption. Therefore, the modified PCE can maintain its dispersion retention capacity for a relatively long time after the initial dispersion is established, eliminating the later-stage degradation.

[0028] The synergistic effect of the two effects resulted in Poly(MAST)-32 having a flowability loss rate of only 18.4% within 120 minutes, and it did not exhibit the characteristic of first increasing and then decreasing throughout the process, while the flowability of the unmodified PCE in the comparative example began to decline continuously after 15 minutes.

[0029] 4-Sulfocal[6]aromatics, as supramolecular host compounds, exert their host-guest recognition function on the cement hydration process mainly through the following pathways: First, ion chelation and regulation. The inner wall of the cup-shaped cavity (about 0.7 nm) of calix[6]arene is composed of multiple phenolic hydroxyl groups and sulfonic acid groups, which have electron-rich properties and can encapsulate or adsorb Ca in the solution through host-guest recognition. 2+ Plasma. This chelation effect temporarily reduces the Ca concentration in the liquid phase. 2+ The supersaturation of the calix[6] aryl hydrocarbons has a certain regulatory effect on the early hydration of minerals such as C3S (tricalcium silicate), and plays a role similar to a retarder. However, in this invention, the calix[6] aryl hydrocarbons are part of the PCE side chain (rather than free molecules), and their cavities may be partially occupied by PEG segments or constrained by polymer chains, and the ion chelation effect is weaker than that of free calix aryl hydrocarbon molecules. Therefore, in the system of this invention, the regulatory effect of calix[6] aryl hydrocarbons on cement hydration is not the dominant effect, but rather the main role is to resist mud at steric cavities and accelerate adsorption.

[0030] Second, the template effect of hydration products. Calixarene derivatives can serve as supramolecular templates or organic frameworks to guide the nucleation and growth of hydration products (such as ettringite AFt and CSH gel). In this invention, the calix[6]arene groups on the PCE molecules anchored to the surface of cement particles may form an ordered region on the particle surface, providing preferred sites for the nucleation of CSH gel, which helps to form a more uniform and dense microstructure and makes a positive contribution to the later strength development.

[0031] Third, the contribution of sulfonic acid groups to early strength. The sulfonic acid groups (-SO3H) on the calixarene skeleton enhance the hydrophilicity and dispersibility of the molecules, allowing cement particles to be more fully dispersed in the early hydration stage, increasing the hydration reaction area, and thus promoting the development of early strength. This effect is reflected in the fact that the 3-day compressive strength of Example 2 (55.2 MPa) is better than that of Comparative Example 1 (38.2 MPa).

[0032] Furthermore, in order to synthesize the above series of copolymers, the present invention provides a calixarene functional monomer with specific cavity size and functional group modification: 4-sulfonylcalix[6]arene monoene, which is prepared by the following steps: In the first step, 6.04 g (5.41 mmol) of 4-sulfonylcalix[6]arene was added to the reaction flask. After purging the system with argon, dichloromethane (100 mL) and triethylamine (1.17 g, 11.56 mmol, 2.14 equivalents) were added sequentially as a reaction solvent and as an acid-binding agent. The mixture was stirred to ensure that the substrate was fully dissolved. The amount of triethylamine used was 2.14 equivalents, which was sufficient to neutralize the hydrogen chloride generated during the reaction and prevent side reactions from occurring.

[0033] In the second step, the reaction system was placed in an ice-water bath at 0°C. A solution of dichloromethane (20 mL) containing acryloyl chloride (4.00 g, 44.19 mmol, 8.17 equivalents) was slowly added dropwise to the reaction system through a constant pressure dropping funnel while stirring. The amount of acryloyl chloride added was 8.17 equivalents. An excess acryloyl chloride strategy was adopted to drive the complete conversion of the esterification reaction and improve the yield of the monoesterification product. The dropping rate was controlled so that the dropping process lasted for 0.5 to 1 hour to prevent excessively high local concentrations from causing side reactions or violent exothermic reactions.

[0034] The third step is to remove the ice-water bath and continue stirring the reaction system at room temperature for 12 hours. The 4-sulfonylcalix[6]arene molecule contains multiple phenolic hydroxyl groups, but by controlling the feed ratio and reaction conditions of acryloyl chloride, this invention mainly obtains monoesterification products—that is, only one phenolic hydroxyl group of the calixarene skeleton is introduced with an acrylate double bond, while the remaining phenolic hydroxyl groups are retained to maintain the water solubility of the molecule and its subsequent copolymerization activity.

[0035] Fourth, add a small amount of water or saturated NH4Cl solution to the reaction flask to quench any unreacted acryloyl chloride. Acryloyl chloride decomposes in water into acrylic acid and hydrogen chloride, thus terminating the reaction.

[0036] Fifth step: Transfer the reaction solution to a separatory funnel, extract with dichloromethane, and collect the organic phase; wash successively with dilute hydrochloric acid (1M) to remove excess triethylamine and its hydrochloride, wash with saturated NaHCO3 solution to neutralize residual acidic substances, wash with saturated brine to remove water-soluble impurities; dry the organic phase with anhydrous Na2SO4 to remove residual moisture.

[0037] Step 6: After filtration, the solvent was removed by rotary evaporation at low temperature to obtain the crude product; purification was performed by column chromatography (SiO2, V(n-hexane):V(ethyl acetate) = 5:1 to 1:1) to obtain 4-sulfonylcalix[6]aromatic monoene (hereinafter referred to as monomer M) with a yield of 72%. The monomer M has the following structural features: the calix[6]aromatic skeleton provides a cavity size of about 0.7 nm, the sulfonyl group (-SO3H) provides hydrophilicity and anchoring ability, and the acrylate double bond provides a polymerizable group.

[0038] The root cause of the clay intercalation problem: Polycarboxylate superplasticizer (PCE) has a comb-like molecular structure, with a main chain of alkyl carbon chains containing carboxyl groups and long polyethylene glycol (PEG) side chains. In cement paste, the carboxyl groups of PCE molecules are anchored to the surface of cement particles, while the PEG side chains extend into the solution, creating a steric hindrance effect that prevents the aggregation of cement particles, thus achieving dispersion. However, when the aggregate contains clay minerals (especially montmorillonite group minerals), the PEG side chains spontaneously intercalate into the interlayer domains of montmorillonite. Montmorillonite is a 2:1 type layered silicate mineral with exchangeable cations (such as Na+) in its interlayers. + Ca 2+ Montmorillonite contains expandable interlayer spaces (approximately 0.3–0.6 nm, which can expand to 1.0–2.0 nm after hydration). PEG segments bind to interlayer cations via ion-dipole interactions, driving an intercalation reaction that leads to the consumption of PCE molecules—side chains are fixed within the clay layers, unable to exert steric hindrance, resulting in a significant reduction in effectively dispersed components. Montmorillonite adsorbs approximately 2–3 times more PCE than cement particles, and the intercalation reaction can increase the interlayer spacing of montmorillonite by more than 12%.

[0039] The present invention selects 4-sulfonylcalix[6] aromatic hydrocarbon as the steric hindrance group, and the design basis is as follows: First, calixarene has a rigid cyclic skeleton structure (formed by phenol units connected by methylene bridges), unlike flexible chain molecules. Its three-dimensional volume is relatively fixed in solution, forming an incompressible spatial barrier. When calixarene is covalently connected to the PCE main chain and serves as part of the side chain, its rigid umbrella-shaped skeleton forms a physical barrier between clay layers. Even if the PEG chain segments have an intercalation tendency, the large calixarene skeleton cannot enter the montmorillonite interlayer (interlayer gap is about 0.3 to 2.0 nm, while the molecular size of calixarene[6] is about 1.5 nm × 1.0 nm), thereby anchoring the side chain and preventing it from intercalating into the interlayer.

[0040] Second, the cavity size of calix[6]arene (approximately 0.7 nm) is larger than that of calix[4]arene (approximately 0.5 nm), resulting in a stronger steric hindrance effect; however, it is more moderate compared to calix[8]arene (approximately 1.0 nm), so as not to excessively affect the water solubility of the molecules and the adsorption rate on the surface of cement particles. Comparative experiments of the present invention confirm (see the comparison between Comparative Example 8 and Example 2) that the anti-mud properties of calix[6]arene-modified PCE are significantly better than those of calix[4]arene-modified PCE.

[0041] Third, the sulfonyl group (-SO3H) on the calix[6] aromatic skeleton has a dual function: on the one hand, it enhances the hydrophilicity of the molecule and promotes the rapid adsorption of water-reducing agent molecules on the surface of cement particles; on the other hand, the sulfonic acid group can react with Ca on the surface of cement particles. 2+ A network reaction occurs, forming a stable anchor point.

[0042] Fourth, compared with existing technologies that modify PCE with β-cyclodextrin (cavity of approximately 0.6 nm), calixarenes not only possess a cavity structure, but also exhibit greater rigidity and thermal stability, and have more chemical modification sites (phenolic hydroxyl groups can undergo various functionalization reactions), resulting in superior flexibility and controllability in molecular design. This invention introduces double bonds through acryloyl chloride esterification followed by direct copolymerization, achieving higher synthesis efficiency and more controllable product structure compared to the existing two-step chlorination-grafting method.

[0043] Optimal Selection of Calicoarylene Ratio: A series of experiments in this invention show that there is an optimal range for the anti-sludge performance of modified PCE based on the caliciarylene ratio. The fluidity retention rate of 1.5% montmorillonite in Poly(MAST)-21 (caliciarylene ratio 21%) was 71.1%, in Poly(MAST)-26 it was 76.5%, in Poly(MAST)-32 it reached 84.2%, and in Poly(MAST)-39 it was 80.9%, showing a trend of first increasing and then decreasing. The underlying mechanism is as follows: When the caliciarylene ratio is too low, the number of sterically hindered side chains on the PCE molecular chain is insufficient, failing to effectively cover and shield all PEG side chains, and some PEG segments can still undergo intercalation adsorption; when the caliciarylene ratio is too high, the dense rigid side chains on the PCE molecular chain make the molecular conformation rigid, reducing the adsorption rate and amount of molecules on the cement particle surface, and excessive caliciarylene side chains may entangle with each other, weakening the dispersion effect. Poly(MAST)-32 (32%) achieves the optimal balance between steric hindrance and molecular compliance in this series.

[0044] This invention also provides a method for preparing the aforementioned low-carbon ultra-high performance concrete, which uses a cement mortar mixer, and the specific steps are as follows: The first step is to add 100 portions of pre-treated tunnel boring machine excavated soil to the mixing pot.

[0045] The second step involves adding silicate cement (6-10 parts), S95 grade granulated blast furnace slag (2-6 parts), and fly ash (1-2 parts) in sequence. The mixer is then turned on and dry-mixed for 30 seconds to ensure the powders and slag particles are initially and evenly mixed. This dry-mixing step facilitates the even distribution of the powders on the surface of the slag particles, preventing clumping after the addition of water.

[0046] The third step involves pre-dissolving the alkali activator (2 parts) with the mixing water (25-35 parts) in a beaker. After the alkali activator is completely dissolved, the mixture is added to a stirrer. This pre-dissolution step ensures the full activation of the alkali activator and avoids uneven dissolution of the solid alkali activator, which could lead to localized excessively high or low alkalinity.

[0047] The fourth step is to add 2 to 2.5 parts of Poly(MAST) series calixarene modified polycarboxylate superplasticizer.

[0048] The fifth step involves starting the mixer and initially mixing at low speed (140±5 r / min rotation, 62±5 r / min revolution) for 90 seconds to fully wet the slurry and achieve initial fluidization. Then, mix at high speed (285±10 r / min rotation, 125±10 r / min revolution) for 60 seconds to fully disperse the components under strong shear, resulting in a homogeneous low-carbon ultra-high-performance concrete mixture. The low-speed mixing stage primarily achieves macroscopic mixing, while the high-speed mixing stage achieves microscopic dispersion and particle deagglomeration.

[0049] The low-carbon properties and mechanical performance of the low-carbon UHPC of this invention originate from the synergistic effect of multiple components: First, the geological polymerization and activation of tunnel boring machine (TBM) slag. TBM slag contains abundant amorphous SiO2 and Al2O3 (mainly derived from the weathering products of clay minerals and feldspar). In the strongly alkaline environment (pH>13) provided by the alkali activator (NaOH / Na2SiO3), silicon-oxygen bonds (Si-O-Si) and aluminum-oxygen bonds (Al-O-Si) break, generating silicate ions (H3SiO4). - H2SiO4 2- ) and aluminate ions (Al(OH)4) - These ions gradually form aluminosilicate polymers (polyaluminosilicates) with a three-dimensional network structure through a condensation reaction. The reaction equation can be expressed as: n(Si2O5,Al2O2)+nSiO2+4nH2O+nOH - →n(AlO4·SiO4·SiO2·4H2O) - ; This geological polymerization reaction can be carried out at room temperature without the need for high-temperature calcination, and its carbon emissions are far lower than those of the two-grind-one-calcination process for silicate cement clinker.

[0050] Second, the pozzolanic effect of fly ash. The active SiO2 and Al2O3 in fly ash undergo a pozzolanic reaction under the stimulation of Ca(OH)2 generated during cement hydration, producing additional CSH gel. Simultaneously, the glass microsphere morphology (spherical particles) in fly ash acts as a ball bearing in the freshly mixed slurry, reducing interparticle friction and improving the fluidity of the mixture.

[0051] Third, calcium supplementation from slag. Slag is rich in CaO (approximately 35-45%), which releases calcium under alkaline activation conditions. 2+ The slag reacts with the aluminosilicate ions released from fly ash and slag to form CSH and CASH gels. The addition of slag compensates for the low calcium content of fly ash and tunnel slag, maintaining the calcium-silicon ratio (C / S) of the system within a suitable range (approximately 1.2–1.8), which is conducive to the formation of stable hydration products.

[0052] Fourth, the multi-level particle packing effect. The shield tunneling slag (fine aggregate, particle size 0.075-3mm), fly ash (microspheres, d50≈29μm), slag (d50≈15μm) and cement (d50≈20μm) form a multi-level particle packing system from micron to millimeter, achieving the densest packing, reducing the amount of slurry required to fill the pores, and promoting strength development.

[0053] Fifth, the quantitative basis for low carbon emissions. The carbon emissions per cubic meter of UHPC according to this invention are 175–220 kg CO2 / m³. 3 Compared to traditional UHPC (485kg CO2 / m³), 3 ) Reduced by 54.6% to 63.9%. Sources of emission reduction include: (1) a significant reduction in cement consumption (traditional UHPC 600-900 kg / m³). 3 →This invention is 180~300kg / m 3 (2) The carbon emission factors of shield tunnel slag and fly ash as solid waste are 0 or extremely low (0 for slag, 19.6 kg CO2e / t for fly ash); (3) Although the carbon emission factors of the alkaline activator are relatively high (1601 for sodium hydroxide, 1140 kg CO2e / t for water glass), the dosage is extremely low (2 parts / formula, approximately 17 kg / m³). 3 The impact on total carbon emissions is limited.

[0054] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention modifies polycarboxylate superplasticizer using 4-sulfonylcalix[6]arene. The rigid, large-volume skeleton (cavity of about 0.7 nm) of calix[6]arene forms a steric hindrance effect, effectively inhibiting the intercalation and adsorption of PEG branches of PCE into the montmorillonite layers, thus solving the technical problem of the significant decrease in dispersion ability of traditional PCE in mud-containing systems. The sulfonic acid groups of calixarene also enhance the hydrophilicity of the molecules, promoting rapid adsorption on the surface of cement particles. Experiments show that when the montmorillonite content is 1.5%, the fluidity retention rate of modified PCE paste reaches 84.2%, which is significantly better than the 45.7% of traditional PCE and the 61.2% of 4-tert-butylcalix[4]arene-modified PCE.

[0055] 2. This invention enhances the extensibility of the polymer molecular structure through calixarene modification, accelerates the initial adsorption rate of PCE on the surface of cement particles, and, together with the steric hindrance effect to inhibit clay adsorption, synergistically eliminates the common plasticization delay phenomenon in the APEG-PCE system. The fluidity loss rate is only 18.4% within 120 min, and there is no characteristic of first increasing and then decreasing.

[0056] 3. This invention makes extensive use of shield tunneling excavated soil (100 parts / formulation, approximately 850 kg / m³). 3 UHPC uses fly ash (1-2 parts / formula) to replace natural aggregates and part of the cement, achieving high-value utilization of solid waste through the synergistic effect of alkali-activated geological polymerization and cement hydration. The carbon emission per cubic meter of UHPC is 175-220 kg CO2 / m³. 3 Compared to traditional UHPC (485kg CO2 / m³), 3 (This represents a decrease of 54.6% to 63.9%).

[0057] 4. This invention utilizes a rational gradation of a cement-slag-fly ash ternary cementitious system, combined with the excellent dispersion properties of calixarene-modified PCE, to achieve a 28-day compressive strength of 118.7–145.6 MPa and a flexural strength of 15.2–19.8 MPa, meeting the UHPC performance standard (≥120 MPa). It also possesses high mechanical properties, low cost, and environmentally friendly characteristics.

[0058] 5. This invention uses conventional cement mortar mixing equipment, eliminating the need for high-temperature and high-pressure curing. It can achieve ultra-high performance at room temperature, making it suitable for large-scale production and engineering applications. Detailed Implementation

[0059] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0060] Preparation Example 1: Poly(MAST)-0 (unmodified PCE, monomer M:TPEG=0:100) Raw materials and dosage: TPEG (molecular weight 2400) 131.0 g (0.0546 mol); acrylic acid 11 g; sodium methacrylate sulfonate 2 g; deionized water 160 ml; 30% hydrogen peroxide 1.5 g; ascorbic acid 0.25 g; 3-mercaptopropionic acid 0.5 g; deionized water 75 ml.

[0061] Preparation steps: Dissolve 131.0 g of TPEG in 160 mL of deionized water and add to a four-necked flask. Heat to 60 °C and add 1.5 g of hydrogen peroxide. Prepare solution No. 1 (11 g of acrylic acid and 2 g of sodium methyl allyl sulfonate dissolved in 30 mL of water) and solution No. 2 (0.5 g of 3-mercaptopropionic acid and 0.25 g of ascorbic acid dissolved in 45 mL of water). Maintain 60 °C and add the solutions dropwise over 3 hours and 3.5 hours respectively, stirring continuously for 1 hour after each addition. After cooling, adjust the pH to 6.5–7.0 with 30% NaOH, with a solid content of approximately 40%.

[0062] Preparation Example 2: Poly(MAST)-17 (actual molar ratio of monomer M:TPEG ≈ 0.17:0.83) Raw materials and dosage: 124.5 g (0.0519 mol) of TPEG (molecular weight 2400); 12.0 g (0.0104 mol, based on molecular weight 1151.73) of monomer M; the rest is the same as in preparation example 1.

[0063] Preparation steps: Same as in Preparation Example 1, except that the TPEG in the pre-prepared monomer solution is replaced with a mixture of 124.5 g of TPEG and 12.0 g of monomer M.

[0064] Molar ratio calculation: TPEG molar amount 0.0519 mol (83.3%), monomer M molar amount 0.0104 mol (16.7%), actual molar ratio 0.17:0.83.

[0065] Preparation Example 3: Poly(MAST)-22 (actual molar ratio of monomer M:TPEG ≈ 0.22:0.78) Raw materials and dosage: TPEG (molecular weight 2400) 117.9 g (0.0491 mol); monomer M 15.6 g (0.0135 mol); the rest is the same as in preparation example 1.

[0066] Preparation steps: Same as in Preparation Example 1.

[0067] Molar ratio calculation: TPEG molar amount 0.0491mol (78.4%), monomer M molar amount 0.0135mol (21.6%), actual molar ratio 0.22:0.78.

[0068] Preparation Example 4: Poly(MAST)-26 (Preferred example, actual molar ratio of monomer M:TPEG ≈ 0.26:0.74) Raw materials and dosage: 111.3 g (0.0464 mol) of TPEG (molecular weight 2400); 19.2 g (0.0167 mol) of monomer M; the rest is the same as in preparation example 1.

[0069] Preparation steps: Same as in Preparation Example 1.

[0070] Molar ratio calculation: TPEG molar amount 0.0464mol (73.5%), monomer M molar amount 0.0167mol (26.5%), actual molar ratio 0.26:0.74.

[0071] Preparation Example 5: Poly(MAST)-33 (actual molar ratio of monomer M:TPEG ≈ 0.33:0.67) Raw materials and dosage: 102.5 g (0.0427 mol) of TPEG (molecular weight 2400); 24.0 g (0.0208 mol) of monomer M; the rest is the same as in preparation example 1.

[0072] Preparation steps: Same as in Preparation Example 1.

[0073] Molar ratio calculation: TPEG molar amount 0.0427mol (67.2%), monomer M molar amount 0.0208mol (32.8%), actual molar ratio 0.33:0.67.

[0074] To systematically verify the full scope of protection of the low-carbon ultra-high performance concrete of this invention, this embodiment adopts a multi-factor system test design with the following parameters: Table 1. Key factors for orthogonal experiments:

[0075] Example 1 (lower limit of cement usage: 6 parts; upper limit of water-cement ratio: around 0.45): 100 parts of tunnel boring machine excavation soil; 6 parts of P·O 42.5 cement; 4 parts of slag; 1.5 parts of fly ash; 2 parts of alkali activator (a mixture of 2.8 modulus water glass and 10 mol / L NaOH in a 3:1 ratio); 2.2 parts of Poly(MAST)-26 water-reducing agent; 29 parts of water. Water-cement ratio = 29 ÷ (6 + 4 + 1.5) = 0.43.

[0076] Preparation method: (1) The shield tunnel slag is cleaned, slurry is adjusted (moisture content 55%), sieved with 2mm, and dehydrated by pressure filtration to a moisture content of 38% and set aside; (2) The pretreated shield tunnel slag is added to a cement mortar mixer; (3) Cement, slag and fly ash are added in sequence and dry-mixed for 30 seconds; (4) Alkali activator is dissolved in the mixing water and added to the mixer; (5) Poly(MAST)-26 water-reducing agent is added; (6) Mix at low speed for 90 seconds and at high speed for 60 seconds, and then discharge.

[0077] Example 2 (preferred cement dosage: 8 parts): 100 parts shield tunneling slag; 8 parts P·O 42.5 cement; 4 parts slag; 1.5 parts fly ash; 2 parts alkali activator; 2.2 parts Poly(MAST)-26 water-reducing agent; 28 parts water. Water-cement ratio = 28 ÷ (8 + 4 + 1.5) = 0.37. Preparation method is the same as in Example 1.

[0078] Example 3 (Cement usage maximum 10 parts, P·O 52.5 cement): 100 parts shield tunneling slag; 10 parts P·O 52.5 cement; 4 parts slag; 1.5 parts fly ash; 2 parts alkali activator; 2.2 parts Poly(MAST)-26 water-reducing agent; 26 parts water. Water-cement ratio = 26 ÷ (10 + 4 + 1.5) = 0.32. Preparation method is the same as in Example 1.

[0079] Example 4 (maximum 6 parts slag, maximum 2 parts fly ash, NaOH alkali activator): 100 parts shield tunneling slag; 8 parts P·O42.5 cement; 6 parts slag; 2 parts Grade I fly ash; 2 parts alkali activator (NaOH 12mol / L); 2.5 parts Poly(MAST)-33 water-reducing agent; 30 parts water. Water-cement ratio = 30 ÷ (8 + 6 + 2) = 0.44. Preparation method is the same as in Example 1.

[0080] Example 5 (2 parts slag, 1 part fly ash): 100 parts shield tunneling slag; 8 parts P·O 42.5 cement; 2 parts slag; 1 part Class II fly ash; 2 parts alkali activator; 2.0 parts Poly(MAST)-26 water-reducing agent; 27 parts water. Water-cement ratio = 27 ÷ (8 + 2 + 1) = 0.41. Preparation method is the same as in Example 1.

[0081] Example 6 (maximum water-reducing agent dosage 2.5 parts, Poly(MAST)-22): 100 parts shield tunneling slag; 8 parts P·O 42.5 cement; 4 parts slag; 1.5 parts fly ash; 2 parts alkali activator; 2.5 parts Poly(MAST)-22 water-reducing agent; 28 parts water. Water-cement ratio 0.37. Preparation method is the same as in Example 1.

[0082] Example 7 (lower limit of water-reducing agent dosage 2.0 parts): 100 parts shield tunnel slag; 8 parts P·O 42.5 cement; 4 parts slag; 1.5 parts fly ash; 2 parts alkali activator; 2.0 parts Poly(MAST)-26 water-reducing agent; 28 parts water. Water-cement ratio 0.37. Preparation method is the same as in Example 1.

[0083] Example 8 (lower limit of water-cement ratio 0.30): 100 parts shield tunneling slag; 10 parts P·O 52.5 cement; 4 parts slag; 1.5 parts fly ash; 2 parts alkali activator; 2.5 parts Poly(MAST)-26 water-reducing agent; 24 parts water. Water-cement ratio = 24 ÷ (10 + 4 + 1.5) = 0.30. The preparation method is the same as in Example 1.

[0084] Example 9 (water-cement ratio upper limit 0.45): 100 parts shield tunneling slag; 6 parts P·O 42.5 cement; 2 parts slag; 1 part fly ash; 2 parts alkali activator; 2.2 parts Poly(MAST)-17 water-reducing agent; 32 parts water. Water-cement ratio = 32 ÷ (6 + 2 + 1) = 0.44. Preparation method is the same as in Example 1.

[0085] Based on the experimental conditions of Example 2, the following single-factor experiments were conducted: Comparative Example 1 (unmodified water-reducing agent control, corresponding ratio 0:100): The difference from Example 2 is that Poly(MAST)-0 is used instead of Poly(MAST)-26, otherwise the same.

[0086] Comparative Example 2 (Control without Shield Tunneling Excavation): Differences from Example 2: No shield tunneling excavation was used; instead, 100 parts of ISO standard sand were used; the cement content was increased to 20 parts; and no alkali activator was used. All other aspects remained the same.

[0087] Comparative Example 3 (water-reducing agent dosage below the lower limit): The difference from Example 2 is that the dosage of Poly(MAST)-26 water-reducing agent was reduced to 1.0 part, and the rest were the same.

[0088] Comparative Example 4 (water-reducing agent dosage higher than the upper limit): The difference from Example 2 is that the dosage of Poly(MAST)-26 water-reducing agent is increased to 4.0 parts, and the rest are the same.

[0089] Comparative Example 5 (water-to-gel ratio higher than the upper limit of 0.45): The difference from Example 2 is that the amount of water used is increased to 45 parts (water-to-gel ratio 0.56), and the rest are the same.

[0090] Comparative Example 6 (water-to-gel ratio below the lower limit of 0.30): The difference from Example 2 is that the amount of water used is reduced to 22 parts (water-to-gel ratio = 22 ÷ 13.5 = 0.26), and the rest are the same.

[0091] Comparative Example 7 (cement dosage below the lower limit of 6 parts): The difference from Example 2 is that the cement dosage is reduced to 4 parts, the slag dosage is increased to 8 parts (the total amount of cementitious materials remains unchanged at 12 parts), and the rest are the same.

[0092] Comparative Example 8 (cement usage exceeds the upper limit by 10 parts): The difference from Example 2 is that the cement usage is increased to 14 parts, the slag usage is reduced to 0 parts, and the rest are the same.

[0093] Comparative Example 9 (High-proportion control of Poly(MAST)-33): The difference from Example 2 is that Poly(MAST)-33 is used instead of Poly(MAST)-26, otherwise the same.

[0094] Comparative Example 10 (Prior art cup[4] aromatic modification control, corresponding to comparative document CN113583190A): The difference from Example 2 is that 4-tert-butylcalix[4] aromatic modified PCE (prepared according to CN113583190A method: first chlorination reaction of terminal hydroxyl polyether macromonomer, then grafting with 4-tert-butylcalix[4] aromatic) is used instead of Poly(MAST)-26, the rest are the same.

[0095] The products of Examples 1-9 and Comparative Examples 1-10 were subjected to performance tests according to the following test methods: 1. Workability test: Refer to GB / T 50080-2016 to test the slump and spread of fresh concrete.

[0096] Table 2. Performance of each embodiment and comparative example

[0097] Data Analysis: Effect of Cement Dosage (Examples 1-3): As the cement dosage increased from 6 parts to 10 parts, the initial slump increased from 235 mm to 255 mm. This was because the increased cement dosage increased the total volume of the paste, improving fluidity. When the water-cement ratio decreased from 0.43 to 0.32, the slump actually increased. This is because the increased cement dosage increased the paste volume, which was sufficient to offset the negative impact of the decreased water-cement ratio on fluidity. In Example 1 (6 parts cement), the initial slump was 235 mm, and the 1-hour loss rate was 6.4%, which still met the construction requirements, indicating that the water-reducing agent of this invention still has good dispersion and retention properties even with low cement dosage.

[0098] Effects of slag / fly ash (comparison of Examples 4-5): When the slag content increased from 4 parts to 6 parts and the fly ash content increased from 1.5 parts to 2 parts, the initial slump increased from 245 mm (Example 2) to 250 mm (Example 4). This was because the spherical particle shape and good gradation of slag and fly ash improved the fluidity of the slurry. When the slag content increased from 2 parts to 4 parts (Example 5 → Example 2), the initial slump increased from 240 mm to 245 mm, a smaller increase, indicating that the improvement in fluidity by slag exhibits a diminishing marginal effect.

[0099] Effect of water-reducing agent type (comparison of Examples 2, 6, and 9): Poly(MAST)-26 (0.26:0.74) had an initial slump of 245 mm and a 1-hour loss rate of 6.1%; Poly(MAST)-22 (0.22:0.78) had an initial slump of 252 mm and a 1-hour loss rate of 4.8%, showing slightly better short-term fluidity; Poly(MAST)-17 (0.17:0.83) had an initial slump of 248 mm and a 1-hour loss rate of 5.2%. All three were better than the 33.3% loss rate of Comparative Example 1 (unmodified PCE), but Poly(MAST)-26 was the best in terms of anti-sludge retention (see Table 4), indicating that the ratio of calixarenes has different effects on the optimal range of dispersibility and anti-sludge properties.

[0100] Effect of water-reducing agent dosage (comparison between Example 2 and Examples 6-7): When the dosage increased from 2.0 parts to 2.5 parts, the initial slump increased from 235 mm to 252 mm, and the 1-hour loss rate decreased from 7.2% to 4.8%, indicating that increasing the dosage can improve the initial dispersibility and retention. However, when the dosage was too low (Comparative Example 3, 1.0 parts), the initial slump was only 165 mm, and the 1-hour loss rate was 21.2%, indicating that the dispersion effect was insufficient when the dosage was below 2.0 parts.

[0101] Effect of water-cement ratio (comparison of Examples 8-9 and Comparative Examples 5-6): When the water-cement ratio increased from 0.30 to 0.45, the initial slump increased from 225 mm to 248 mm, improving fluidity. When the water-cement ratio was below 0.30 (Comparative Example 6, 0.26), the slurry viscosity was too high (initial slump 185 mm), resulting in insufficient workability; when the water-cement ratio was above 0.45 (Comparative Example 5, 0.56), although the initial fluidity was excellent (285 mm), there was a risk of segregation and strength loss.

[0102] Cup[4] Comparison (Comparative Example 10): The initial slump of the cup[4] modified was 225 mm, and the loss rate was 13.3% in 1 hour, which was worse than that of the cup[6] modified (Example 2, 245 mm, loss rate 6.1%), verifying the expectation that cup[6] aromatics provide better steric hindrance effect due to the larger cavity.

[0103] 2. Mechanical property testing: Refer to GB / T 50081-2019, specimen size 100mm×100mm×100mm, standard curing (20±2℃, RH≥95%).

[0104] Table 3. Mechanical properties of each embodiment and comparative example

[0105] Data Analysis: Relationship between cement dosage and strength (Examples 1-3): The 28-day compressive strength increased linearly with the cement dosage increasing from 6 parts to 10 parts (118.7 → 145.6 MPa), with a correlation coefficient R. 2 ≈0.99. Example 1 (118.7MPa) is slightly lower than the UHPC standard (≥120MPa), indicating that 6 parts of cement meet the lower limit for ultra-high performance; Example 2 (132.5MPa) and Example 3 (145.6MPa) meet the standard.

[0106] The optimal ratio of slag to fly ash (comparison of Examples 2, 4, and 5): 4 parts slag + 1.5 parts fly ash (Example 2) yielded a 28-day strength of 132.5 MPa, superior to 6 parts slag + 2 parts fly ash (Example 4, 126.8 MPa) and 2 parts slag + 1 part fly ash (Example 5, 130.2 MPa). While replacing cement with excessive slag and fly ash reduces carbon emissions, the lower cementitious activity of fly ash leads to a decrease in strength.

[0107] Effect of water-binder ratio (comparison of Examples 2, 8-9 and Comparative Examples 5-6): The 28-day strength was 138.8 MPa at a water-binder ratio of 0.32 (Example 8), 132.5 MPa at 0.37 (Example 2), and 115.2 MPa at 0.44 (Example 9). The strength decreased by 17.0% when the water-binder ratio increased from 0.32 to 0.44. The strength was only 98.7 MPa at a water-binder ratio of 0.56 (Comparative Example 5), and 100.2 MPa at a water-binder ratio of 0.26 (Comparative Example 6). This indicates that when the water-binder ratio exceeds 0.45, excess free water forms capillaries, significantly reducing strength. When the water-binder ratio is below 0.30, the slurry becomes too thick, leading to poor molding and increased internal defects. Considering both workability and mechanical properties, a water-binder ratio of 0.30–0.45 is the optimal range.

[0108] Effect of water-reducing agent dosage (comparison of Examples 2, 6-7 and Comparative Examples 3-4): The 28-day strengths corresponding to dosages of 2.0%, 2.2%, and 2.5% were 128.5, 132.5, and 131.0 MPa, respectively, showing a trend of first increasing and then leveling off. With a dosage that was too low (1.0%, Comparative Example 3), the strength was only 88.4 MPa, due to insufficient dispersion leading to particle agglomeration and increased porosity. With a dosage that was too high (4.0%, Comparative Example 4), the strength was 128.5 MPa, comparable to Example 7 (2.0%, 128.5 MPa), but economic efficiency decreased and there was a risk of segregation.

[0109] Cup[4] Comparison (Comparative Example 10): 28-day strength 115.8 MPa, lower than 132.5 MPa in Example 2. The cup[4] aromatic cavity is small (0.5 nm), the steric hindrance effect is insufficient, the PEG side chain is still partially intercalated and adsorbed, the effective dispersed components are consumed, and the unevenness of the slurry leads to a decrease in strength.

[0110] 3. Anti-mud performance test: Referring to GB / T 8077-2012, different dosages of sodium-based montmorillonite were added to the cement paste, and the fluidity of the paste was tested (water-cement ratio 0.35, water-reducing agent refractory strength 0.15%). Conventional PCE even completely lost its fluidity at a 1% montmorillonite dosage (-- indicates that it could not be measured).

[0111] Table 4. Flowability of Neat Paste under Different Montmorillonite Contents

[0112] Data Analysis: Verification of montmorillonite intercalation mechanism: When the montmorillonite content is 0.5%, the mobility of Poly(MAST)-0 decreases from 280 mm to 212 mm (a loss of 24.3%), while Poly(MAST)-26 only loses 4.6% (285→272). The adsorption capacity of montmorillonite for PCE is about 2 to 3 times that of cement particles. PCE can undergo intercalation reaction with montmorillonite to increase the interlayer spacing. Poly(MAST)-26 effectively inhibits intercalation adsorption through the steric hindrance of cup [6] aromatics.

[0113] Verification of the optimal range of calixarene ratio: Under the condition of 1.5% montmorillonite, the PCE retention rate of each modified compound was ranked as follows: Poly(MAST)-26 (84.2%) > Poly(MAST)-33 (80.9%) > Poly(MAST)-22 (76.5%) > Poly(MAST)-17 (71.1%) > calix[4] modified (61.2%) > Poly(MAST)-0 (45.7%). Poly(MAST)-26 was significantly better than other ratios, indicating that there is an optimal range of calixarene ratio: too low (0.17:0.83) has insufficient steric hindrance, too high (0.33:0.67) affects molecular flexibility and adsorption efficiency, and 0.26:0.74 is the best balance point.

[0114] Comparison of cup [6] and cup [4]: ​​Under 1.5% montmorillonite, the modification retention rate of cup [4] was 61.2%, which was significantly lower than the lowest value of 71.1% in the cup [6] series (Poly(MAST)-17). This verifies the scientific expectation that the cavity size of cup [6] aromatics (0.7 nm) is larger than that of cup [4] (0.5 nm), and that the steric hindrance effect is stronger.

[0115] The patented product with publication number CN107987231A, a calixarene-modified anti-mud PCE, retains approximately 78-82% of its content at 1% montmorillonite. The present invention, Poly(MAST)-26, retains 90.5% of its content at 1% montmorillonite, and maintains 84.2% even at a higher montmorillonite content (1.5%), demonstrating significant advantages.

[0116] 4. Plasticization Delay Test: The change in fluidity of cement paste (water-cement ratio 0.35, water-reducing agent 0.15%) over time was tested.

[0117] Table 5. Changes in Flowability over Time

[0118] Data Analysis: Characteristic identification of plasticization delay: Poly(MAST)-0's fluidity increased from 275 mm to 285 mm from 0 to 15 min (increase stage, increase of 3.6%), and then continuously decreased to 130 mm at 120 min (decrease stage, total loss of 52.7%), exhibiting typical plasticization delay of the APEG-PCE system. The cause is: the initial PCE adsorption rate is slow, and the dispersion effect is rapidly reduced due to clay adsorption after being established during hydration.

[0119] The mechanism by which calixarene modification eliminates plasticization delay: The flowability of Poly(MAST)-26 decreased from 282 mm to 230 mm within 0 to 120 min, with a loss rate of 18.4%, showing a monotonous decrease throughout without an initial increase followed by a decrease. There are two reasons for this: First, the sulfonic acid groups on the calixarene skeleton enhance hydrophilicity, increasing the initial adsorption rate (flowability of 282 mm at 0 min compared to 275 mm for unmodified). Second, steric hindrance inhibits the continuous consumption of PCE by clay, keeping the effectively dispersed components stable within 120 min.

[0120] Comparison between cup[4] and cup[6]: The modification loss rate of cup[4] was 27.8% (270→195), which was between that of unmodified cup[6] and cup[6], indicating that although cup[4] has some improvement, its effect is not as good as that of cup[6].

[0121] 5. Carbon emission accounting: Calculate the carbon emissions per cubic meter of UHPC during the production stage, referring to the LCA method.

[0122] Table 6. Carbon Emission Calculation for Each Mix Ratio

[0123] Note: The data in the table above are rounded values, and the traditional UHPC benchmark carbon emissions are based on 485 kg CO2 / m³. 3 Carbon emission factors of raw materials: cement 785 kg CO2 / t, slag 26.5, fly ash 19.6, NaOH 1601, water glass 1140 kg CO2e / t.

[0124] Data Analysis: Carbon emission source breakdown: Taking Example 2 as an example, cement usage is 240 kg / m³ 3 Contributes approximately 188 kg CO2 / m³ 3 Alkali activator (17kg / m 3 NaOH and water glass contribute approximately 25 kg CO2 / m³. 3 Total ~213kg / m 3 After deducting the negative carbon effect of solid waste, the net emission is approximately 195 kg / m³. 3 Although the alkaline activator has a high carbon emission factor, its dosage is only 2 parts, so its impact on total emissions is limited.

[0125] Relationship between carbon emission reduction rate and cement usage: Example 1 (cement 180kg / m³) 3 Emission reduction rate of 63.9%, Example 3 (cement 300kg / m³) 3 The emission reduction rate was 54.6%, indicating that the carbon emission reduction mainly came from cement substitution. Comparative Example 8 (cement 420 kg / m³) 3 The emission reduction rate was only 42.3%, which is higher than the 13.4% of Comparative Example 2 (no solid waste), but still lower than the embodiment of the present invention.

[0126] While other technologies utilize industrial waste to prepare low-carbon UHPC, the carbon reduction rate is only about 28.7% when the total amount of fly ash reaches 40%. This invention achieves a carbon reduction of 54.6% to 63.9% by using a higher proportion of solid waste (100 parts of tunnel boring machine slag + fly ash + slag), resulting in superior performance.

[0127] In summary, the novel low-carbon ultra-high performance concrete prepared by this invention has the following characteristics: Excellent anti-mud properties: This invention uses 4-sulfonylcalix[6]aromatics to modify polycarboxylate superplasticizer. The rigid large-volume skeleton of calix[6]aromatics (cavity of about 0.7 nm) forms a steric hindrance effect, which effectively inhibits the intercalation and adsorption of PEG branches of PCE into the montmorillonite layers, thus solving the technical problem of the significant decrease in the dispersion ability of traditional PCE in mud-containing systems. The test shows that when the montmorillonite content is 1.5%, the fluidity retention rate of modified PCE slurry reaches 84.2%, which is significantly better than the 45.7% of traditional PCE and the 61.2% of 4-tert-butylcalix[4]aromatic modified PCE.

[0128] Eliminating plasticization delay: This invention enhances the extensibility of the polymer molecular structure through calixarene modification, accelerates the initial adsorption rate of PCE on the surface of cement particles, and, together with the steric hindrance effect to inhibit clay adsorption, synergistically eliminates the common plasticization delay phenomenon in the APEG-PCE system. The fluidity loss rate is only 18.4% within 120 min, and there is no characteristic of first increasing and then decreasing.

[0129] Low-carbon and environmentally friendly: This invention extensively utilizes tunnel boring machine (TBM) slag (100 parts / formula) and fly ash (1-2 parts / formula) to replace natural aggregates and part of the cement. Through the synergistic effect of alkali-activated geological polymerization and cement hydration, high-value utilization of solid waste is achieved. The carbon emission per cubic meter of UHPC is 175-220 kg CO2 / m³. 3 Compared to traditional UHPC (485kg CO2 / m³), 3 (This represents a decrease of 54.6% to 63.9%).

[0130] Excellent overall performance: This invention achieves a 28-day compressive strength of 118.7–145.6 MPa and a flexural strength of 15.2–19.8 MPa through a rational gradation of the cement-slag-fly ash ternary cementitious system, combined with the excellent dispersion performance of calixarene-modified PCE. It meets the UHPC performance standard (≥120 MPa) and combines high mechanical properties with low cost and environmental friendliness.

[0131] The preparation process is simple: This invention uses conventional cement mortar mixing equipment, which does not require high temperature and high pressure curing. It can obtain ultra-high performance at room temperature, making it suitable for large-scale production and engineering applications.

[0132] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A low-carbon ultra-high performance concrete, characterized in that, The raw materials include the following by weight: 100 parts of shield tunnel slag, 6-10 parts of silicate cement, 2-6 parts of slag, 1-2 parts of fly ash, 2 parts of alkali activator, 2-2.5 parts of calixarene-modified polycarboxylate superplasticizer, and 25-35 parts of water; the shield tunnel slag has a moisture content of ≤40% and a particle size of ≤3mm; the calixarene-modified polycarboxylate superplasticizer has a side chain containing 4-sulfonylcalix[6] aromatic structural units.

2. The low-carbon ultra-high performance concrete according to claim 1, characterized in that, The calixarene-modified polycarboxylate superplasticizer is prepared by free radical copolymerization of 4-sulfonylcalix[6]arene monoene and isopentenyl polyoxyethylene ether in a molar ratio of 0.17:0.83 to 0.33:0.

67. The comonomers also include acrylic acid and sodium methacrylate.

3. The low-carbon ultra-high performance concrete according to claim 2, characterized in that, The 4-sulfonylcalix[6] aromatic monoene was prepared by the following method: 4-sulfonylcalix[6] aromatic hydrocarbon and acryloyl chloride were reacted in a dichloromethane system under the catalysis of triethylamine at 0°C for 0.5 to 1 hour, and then the reaction was continued at room temperature for 12 hours. The mixture was then purified by column chromatography.

4. The low-carbon ultra-high performance concrete according to claim 1, characterized in that, The alkaline activator is sodium silicate, sodium hydroxide, or a mixture thereof; the modulus of sodium silicate is 2.4–3.2, and the concentration of the NaOH solution is 8–12 mol / L.

5. The low-carbon ultra-high performance concrete according to claim 1, characterized in that, The fly ash is Grade I or Grade II fly ash, the cement is P·O 42.5 or P·O 52.5 silicate cement, and the slag is S95 grade granulated blast furnace slag.

6. The low-carbon ultra-high performance concrete according to claim 1, characterized in that, The water-to-binder ratio is 0.30 to 0.

45.

7. The method for preparing low-carbon ultra-high performance concrete according to any one of claims 1 to 6, characterized in that, Includes the following steps: (1) Pretreatment of shield tunnel slag: After collection and removal of impurities, water is added to adjust the slurry to a moisture content of 50% to 60%, and the slag is passed through a 2mm sieve. Mechanical dewatering is carried out by pressure filtration or centrifugation until the moisture content is ≤40% and the particle size is ≤3mm. (2) Add 100 parts of the pretreated shield tunneling slag to the mixer; (3) Add 6-10 parts of silicate cement, 2-6 parts of slag, and 1-2 parts of fly ash in sequence, and dry mix for 30 seconds; (4) Mix 2 parts of alkali activator with 25-35 parts of water and add to a stirrer; (5) Add 2-2.5 parts of calixarene-modified polycarboxylate superplasticizer; (6) Mix at low speed for 90 seconds and at high speed for 60 seconds to obtain low-carbon ultra-high performance concrete.

8. The preparation method according to claim 7, characterized in that, The low-speed stirring speed is 140±5 r / min for rotation and 62±5 r / min for revolution, and the high-speed stirring speed is 285±10 r / min for rotation and 125±10 r / min for revolution.

9. The application of the low-carbon ultra-high performance concrete according to any one of claims 1 to 6 in the preparation of precast components or tunnel grouting materials.

Citation Information

Patent Citations

  • Anti-clay polycarboxylate superplasticizer and preparation method thereof

    CN107987231A

  • 4-tert-butylcalix [4] arene modified polycarboxylate superplasticizer and preparation method thereof

    CN113583190A